The impact of batch shipments on the Economic Lot Scheduling Problem. (June 2016) - Beck, Fabian G.; Glock, Christoph H.
Highlights: We study the Economic Lot Scheduling Problem for the single-machine-multi product case. A lot may be split up into batches, which are shipped individually to the consuming stage. We extend the Common-Cycle-Approach and the Basic-Period-Approach. We modify the assignment procedure of Haessler and Hogue. Abstract: This paper studies the Economic Lot Scheduling Problem (ELSP) for the single-machine-multi-product case. In contrast to earlier research, it assumes that a lot may be split up into batches, which are then shipped individually to the consuming stage. Integrating batch shipments into the ELSP helps to reduce cycle times at the expense of higher transportation costs. This paper selects two popular approaches used in the literature to solve the ELSP, namely the Common-Cycle-Approach of Hanssmann and the Basic-Period-Approach of Haessler and Hogue, extends them to include both equal- and unequal-sized batch shipments, and suggests a solution procedure for each approach. Both model extensions are illustrated using the modified Bomberger and Eilon data sets, and they are compared to the special case where only complete lots are transferred to the next stage. Finally, ideas for future research are presented.